(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study investigates the impact of electronic money (e-money) transactions on the financial health of Indonesian banks with variability of size, assessed through the Risk-Based Bank Rating (RBBR) framework. Bank health indicators include Return on Assets (ROA), Return on Equity (ROE), Capital Adequacy Ratio (CAR), Cost to Income Ratio (CIR), and Loan to Deposit Ratio (LDR). In addition to e-money activity, macroeconomic factors such as inflation and broad money supply (M2) are incorporated as control variables. Using quarterly secondary data from 2021 to 2024 sourced from Bank Indonesia, the Financial Services Authority (OJK), and published bank financial statements, the study employs panel regression with classical assumption testing to ensure model robustness. The results show that e-money transactions significantly enhance bank profitability (ROA and ROE) but negatively affect efficiency, capital adequacy, and liquidity (CIR, CAR, and LDR). Furthermore, money supply (M2) consistently exerts a significant influence across indicators, while inflation demonstrates limited impact, affecting only ROE. These findings highlight the dual role of digital finance: strengthening profitability while simultaneously challenging efficiency and liquidity management. The study contributes to the discourse on digital transformation in banking, providing practical insights for banks in strategic planning, for regulators in safeguarding stability amid innovation, and for academics analyzing the systemic implications of digital finance in emerging markets.